Experimental investigation into dynamic axial impact responses of double hat shaped CFRP tubes. (15th September 2015) - Liu, Qiang; Ou, Zhengyan; Mo, Zhengwei; Li, Qing; Qu, Dapeng
Abstract: This paper aims to explore the dynamic responses and crashing characteristics of double hat shaped tubes made of weave carbon fiber reinforced plastic (CFRP). Experimental investigations were carried out into three different thicknesses and lengths of the composite tubes fabricated by the bladder molding process. Three distinct failure modes, classified as progressive end crushing, mid-length collapse and overlap opening, were observed in the dynamic crushing tests. Unlike continuous splaying fronds observed in the quasi-static tests, dynamic tests exhibited a number of fragment segments in the progressive end crushing mode. It is shown that the ply number was a critical parameter affecting the failure mode and energy absorption capability. The increase in ply number led to increases in the peak load and specific energy absorption (SEA); whereas the tubal length seemed insensitive to energy absorption capability. Compared to the quasi-static cases, the dynamic impact tests resulted in the higher peak load (increased from 46 % to 125 %) and lower SEA (reduced from 21 % to 33 %) for the tested tubes.